2018
DOI: 10.1080/03003930.2018.1473768
|View full text |Cite
|
Sign up to set email alerts
|

Assessing electronic service delivery in municipalities: determinants and financial consequences of e-government implementation

Abstract: In the Netherlands, electronic service delivery has become an important issue in many municipalities. Using the Internet for service delivery is seen as an important element of e-government. Based on 2014-2016 panel data for all Dutch municipalities, we show that there is a large variety among the municipalities in the extent to which they offer their service delivery digitally. By exploring the factors that may explain the differences among the municipalities, some trends can be discerned. Most notably is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
2
36
2
2
Order By: Relevance
“…The factors that encourage or inhibit innovation are examined using a mixed methodological approach (including interviews with city officials and multivariate analysis of a new data set on municipal e-government services). The problem of electronic maturity of municipal government is analyzed in correlation with modern requirements for local self-government in [10]. It also investigated the factors explaining the significant discrepancy among municipalities in the provision of digital services to citizens.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors that encourage or inhibit innovation are examined using a mixed methodological approach (including interviews with city officials and multivariate analysis of a new data set on municipal e-government services). The problem of electronic maturity of municipal government is analyzed in correlation with modern requirements for local self-government in [10]. It also investigated the factors explaining the significant discrepancy among municipalities in the provision of digital services to citizens.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Matrix of the minimum possible values y ij (inf) of the initial indicators of e-maturity of the digital office in terms of both project management knowledge areas and PMO еМ e-maturity levels There are two possible cases: 1) if for the current j-th level of e-maturity, the correspondence to which is investigated, at least one of inequalities (10) is violated, then it is necessary to consistently descend one step below j: = j-1 until conditions (10) are met, with the obvious restriction j ³ 0;…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the models cannot be used for explaining maturity, at best it can be applied for categorizing and descriptive statistics [18] Maturity models are, in general, not explanatory. There are emerging studies that link delivery of e-services to explanatory variables [20] There is a misconceived linearity in the model. This is reflected in the numbering of the stages and the visualization of the stages [6] In many maturity models there is an implicit assumed linearity.…”
Section: Misunderstanding Responsesmentioning
confidence: 99%
“…Public sector deployment of social media has mostly been studied in relation to the democratic goals of transparency, participation, and collaboration (Bertot, Jaeger, & Grimes, 2010;Bonsón, Torres, Royo, & Flores, 2012;Harrison et al 2012;Mergel, 2013). Budding, Faber, & Gradus (2018) showed that based on 2014-2016 panel-data for all Dutch municipalities, there is a large variety among the municipalities in the extent to which they offer their services delivery digitally. Different explanations for the variance in e-government adoption were sought by looking at socio-economic variables.…”
Section: Introductionmentioning
confidence: 99%